Measuring engagement among older adults using a multidimensional approach to communication - Radnan, Madeleine Jessica; Li, Weicong; Stevens, Catherine J.; Hill, Clair; Jones, Caroline (Frontiers in Psychology, 2022)
Characterising older adult engagement is important to determine the effectiveness of interventions. Engagement refers to the occupying of oneself in external stimuli and is observable across multiple dimensions of behaviour. Engagement of older adults is commonly investigated using a single behavioural dimension. There is a dearth of analytical methods that can simultaneously quantify both verbal and non-verbal forms of communication as proxies for engagement. In this article, we present a multidimensional technique to measure engagement of older adults using techniques appropriate for people with varying degrees of dementia. The new analytical approach measures facial movement, lexical use, and prosodic patterns of speech as indices of affective and behavioural outcomes of engagement. Contexts for engagement included a dyadic reminiscence therapy interview and a 12-week technology driven group reminiscence therapy. Illustrative examples of the technique are described from two participants from two different groups in a naturalistic setting. Application of these analytical techniques can enhance measurement precision and further develop the science and evidence base especially for, but not confined to, non-pharmacological interventions.